2020
DOI: 10.3390/ani10071221
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Glucose at Litter Equalization as a Strategy to Increase Energy in Intrauterine Growth Restricted Piglets

Abstract: Hyper-prolific sows give birth to large litters and up to 25% of piglets born have been subjected to intrauterine growth restriction (IUGR). The aim of this study was to test whether an oral administration of glucose impacts the survival rate and body weight gain of IUGR piglets at weaning. Different methods (injection versus oral administration of glucose 6 mL or 12 mL, respectively) were tested on IUGR piglets at litter equalization (i.e., when piglets are handled the first time at 5–20 h after birth). Injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We hypothesized that decreased feed intake after weaning would lead to blood glucose concentrations below normal, therefore increasing mortality rates. Limited research evaluating supplemental glucose has been conducted in wean pigs; however, of the studies available from birth to approximately 30 kg, dosages ranged from 0.30 to 1.75 g/kg body weight ( Manell et al, 2016 ; Kvidera et al, 2017 ; Engelsmann et al, 2019 ; Klaaborg and Amdi, 2020 ). Route of administration (intravenously, subcutaneously, or orally) also varied.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that decreased feed intake after weaning would lead to blood glucose concentrations below normal, therefore increasing mortality rates. Limited research evaluating supplemental glucose has been conducted in wean pigs; however, of the studies available from birth to approximately 30 kg, dosages ranged from 0.30 to 1.75 g/kg body weight ( Manell et al, 2016 ; Kvidera et al, 2017 ; Engelsmann et al, 2019 ; Klaaborg and Amdi, 2020 ). Route of administration (intravenously, subcutaneously, or orally) also varied.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, approximately 30 million of infants are affected by IUGR each year worldwide ( Shen et al, 2018a ). Similarly, 10%–25% of newborn piglets in pig production are classified as IUGR piglets ( Klaaborg and Amdi, 2020 ). In IUGR animals, skeletal muscle is one of the organs most affected by altered blood circulation and perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated more energy-dense supplementation and concluded that a single oral dose of fat-based energy at birth were not enough to improve growth and survival in low birth weight piglets [ 28 ]. Other researchers have tried different interventions such as glucose or colostrum without convincing results [ 12 , 27 ] and it is therefore questionable if it is the quality or the quantity that has an impact. Our suggestion of filling the stomach to about half at each feeding (25 mL kg/BW) is perhaps airing on the cautious side, and a consequence is that the procedure would need to be repeated several times to ensure enough colostrum to gain energy and immunity for survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to increasing litter sizes, up to 40% of sows in a herd are used as nurse sows [ 11 ]. Although this removes litter competition [ 12 ] an insufficient intake of colostrum is one of the main underlying factors affecting early deaths in piglets [ 13 , 14 ]. Therefore, more intense/laboursome management strategies are possibly needed.…”
Section: Introductionmentioning
confidence: 99%